Risk management in relation to project success on the construction projects in UAE - MURAD, MOHAMMED HASSAN (2018)
The risk management is one of the most important process in the project management. Recently, the focus increased in the risk management as it is crucial to achieve successful projects. In this dissertation the relationship between the risk management and project success is examined in the construction sector in the UAE. A model was created to examine this relation by reviewing and conducting comparative analysis between various risk management models and standards. Then, questionnaire was developed and sent to the respondent from the construction field, the obtained data were analyzed using SPSS. Where the reliability, correlation and regression test took place. In this paper five hypotheses were proposed and all of them were examined and found valid. As a result, one of the most important process in the risk management process is identifying the risk as it is the first process and without it the following process can’t be carried out.